Kualitas Minyak Bekas Penggorengan Jajanan Berdasarkan Kadar Asam Lemak Bebas Di Kelurahan Amban Kecamatan Manokwari Barat - Charlota Angelina Kapitarauw; Bimo Budi Santoso; Darma Santi Darma Santi (Jurnal Natural, 2023)
Analysis of the quality of used frying oil for snacks in the Amban Village, Manokwari Regency has been carried out. Parameters tested were color, water content, free fatty acids and acid number. The results of the analysis of the five samples from the five frying places showed varied results. In plain view the colors of the five samples still met the quality standard, except for sample A. Of the five samples analyzed, the water content of all samples still met the SNI-01-3741-2002 quality standard, which is still below 0.1% (w/b). The acid number content test of the five samples ranged from 0.36 to 1.135 mg KOH/g. Of the five samples tested, two samples exceeded the quality standard requirement 1, namely samples A and D, each with an acid number of 1.005 and 1.135. The free fatty acid content of the five tested samples ranged from 1.67 to 5.67%. There were two samples that exceeded the quality standard (SNI-01-3741-2002), namely samples A and D with acid content of 5.04% and 5.67%, respectively. The test results show that the quality of used frying oil still has 3 samples that meet the quality standards, namely samples B, C and E and 2 samples that do not meet the required quality standards, namely A and D.